Dukungan Orang Tua pada Program Bimbingan Konseling dan Disiplin Siswa - Syuhadatina, Titin; Rosita, Eva; Muhyatun, Muhyatun; Putri, Sari Nusantara (STAI Publisistik Thawalib Jakarta, 2024)
The implementation of character education focused on discipline at MTs Tanwirul Ulum involves the enforcement of school regulations such as morning flag ceremonies, complete uniforms, punctuality, and the active role of guidance counselors in addressing students' behavior that is not yet optimal. The purpose of this study is to explain and describe the support provided by parents and guidance counselors in disciplining students. This research uses a qualitative approach and case study method, utilizing interviews, observations, and documentation. Data analysis includes condensation, data presentation, and conclusion drawing. The results of the study show that parental support in improving the guidance counseling program and student discipline includes open communication with counselors regarding the child's development and issues, involvement in counseling activities, and creating a conducive learning environment at home. Additionally, parents collaborate with the school through regular meetings with the guidance counselors. In improving student discipline, parents set an example of disciplined behavior, participate in school activities, maintain communication with teachers, provide guidance or reprimands when necessary, offer encouragement, praise achievements, establish clear rules at home, and teach empathy and the importance of discipline in life.